1991
DOI: 10.1002/eji.1830210803
|View full text |Cite
|
Sign up to set email alerts
|

Expression of different CD8 isoforms on distinct human lymphocyte subpopulations

Abstract: Human CD8+ lymphocyte subpopulations were analyzed for their expression of CD8 alpha and CD8 beta subunits. Investigations with uncloned peripheral blood lymphocytes as well as cloned human natural killer and T cell subpopulations demonstrate that CD3- natural killer cells, T cell receptor gamma/delta, and CD4+CD8+ T cell clones express exclusively CD8 alpha gene products. Structural analysis of CD8 molecules demonstrates that CD8 alpha+/beta- T lymphocytes surface express 75-kDa CD8 alpha/alpha homodimers whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 44 publications
3
103
0
1
Order By: Relevance
“…6A, virtually all CD3 ϩ CD8 ϩ CD5 ϩ and CD3 ϩ CD8 ϩ CD5 Ϫ lymphocytes stained with an anti-CD8␣ mAb, whereas an anti-CD8 mAb recognizing a CD8 epitope generated by coupling of the ␣-and ␤-chains recognized all CD3 ϩ CD8 ϩ CD5 ϩ cells, but only a fraction of CD3 ϩ CD8 ϩ CD5 Ϫ lymphocytes. As a consequence, we could conclude that a significantly higher ( p Ͻ 0.01) proportion of CD3 ϩ CD8 ϩ CD5 Ϫ cells expressed the ␣␣ form of the CD8 molecule compared with the CD5 ϩ counterpart, which, as expected (38,43,44), mostly expressed the ␣␤ variant of this coreceptor (Fig. 6B).…”
Section: Phenotypic Characterization Of Cd3supporting
confidence: 62%
See 2 more Smart Citations
“…6A, virtually all CD3 ϩ CD8 ϩ CD5 ϩ and CD3 ϩ CD8 ϩ CD5 Ϫ lymphocytes stained with an anti-CD8␣ mAb, whereas an anti-CD8 mAb recognizing a CD8 epitope generated by coupling of the ␣-and ␤-chains recognized all CD3 ϩ CD8 ϩ CD5 ϩ cells, but only a fraction of CD3 ϩ CD8 ϩ CD5 Ϫ lymphocytes. As a consequence, we could conclude that a significantly higher ( p Ͻ 0.01) proportion of CD3 ϩ CD8 ϩ CD5 Ϫ cells expressed the ␣␣ form of the CD8 molecule compared with the CD5 ϩ counterpart, which, as expected (38,43,44), mostly expressed the ␣␤ variant of this coreceptor (Fig. 6B).…”
Section: Phenotypic Characterization Of Cd3supporting
confidence: 62%
“…This finding is somewhat surprising and may help in explaining some experimental and/or clinical observations. The ␣␣ form of CD8 is mostly expressed on NK cells (43,62) and is usually associated with a poor proliferative response to mitogenic stimulation and preferential display of non-MHC-restricted cytotoxic activity (43,63). Indeed, in several repeated attempts we never succeeded in stabilizing in vitro long term CD3 ϩ CD8 ϩ CD5 Ϫ lines or clones; the inability of these cells to undergo substantial in vitro expansion was apparently not due to the production of immunomodulatory cytokines, such as TGF-␤ (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32][33][34][35][36] In the case of melanoma lines, B7 expression appeared to be necessary to induce allogeneic responses; whereas this was not found to be the case here with the RCC-26 renal carcinoma line. Although it has been found that CTL responses directed against tumorassociated antigens could be induced following stimulation with B7-modified melanoma lines, the priming procedures utilized purified CD8 T cells and culture conditions that did not support the development of alloresponses; 32,33 thus, the influence of dominating allospecific CTL on development of tumor-specific CTL could not be assessed in these studies.…”
Section: Discussionmentioning
confidence: 58%
“…CD8 proteins are encoded by two genes, CD8a and CD8b, and expressed on the cell surface as homodimeric CD8aa and heterodimeric CD8ab [16]. Although both CD8aa and CD8ab bind to the classic MHCI molecules and function as coreceptors to enhance recognition of peptide antigens by TCR, CD8ab is apparently more efficient than CD8aa [17][18][19].…”
Section: Introductionmentioning
confidence: 99%